2010
DOI: 10.1021/ja109165f
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis and Confirmation of the Absolute and Relative Stereochemistry of Streptorubin B

Abstract: The enantioselective total synthesis of the pyrrolophane natural product streptorubin B is described. Key steps in the concise route include application of a one-pot enantioselective aldol cyclization/Wittig reaction and an anionic oxy-Cope rearrangement to forge the crucial 10-membered ring. Comparisons between CD-spectra of synthetic and natural samples of streptorubin B, coupled with X-ray crystallography, allowed for the determination of the absolute stereochemistry of this natural product for the first ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
72
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 34 publications
8
72
0
Order By: Relevance
“…Parallel to this study, the first total synthesis of 40 by Thompson et al arrived at the same conclusion of absolute configuration. 92 This investigation first utilised an approach of ring closing metathesis to generate the streptorubin core; however this approach failed, presumably due to ring strain of the desired product. Thus, a new method was developed (Scheme 8) using a Swern oxidation of intermediate 42 (generated from an enantioselective aldol/Wittig reaction of heptanedial) followed by enantioselective addition of a protected alkenyl to furnish 43.…”
Section: Streptorubin B: a Recently Synthesized Antibiotic From Red Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Parallel to this study, the first total synthesis of 40 by Thompson et al arrived at the same conclusion of absolute configuration. 92 This investigation first utilised an approach of ring closing metathesis to generate the streptorubin core; however this approach failed, presumably due to ring strain of the desired product. Thus, a new method was developed (Scheme 8) using a Swern oxidation of intermediate 42 (generated from an enantioselective aldol/Wittig reaction of heptanedial) followed by enantioselective addition of a protected alkenyl to furnish 43.…”
Section: Streptorubin B: a Recently Synthesized Antibiotic From Red Pmentioning
confidence: 99%
“…X-ray crystallography of HCl salts for both synthetic and natural products confirmed the absolute configuration of the primary product as 40 using anomalous dispersion calculations. 92 Scheme 8: The first total-synthesis of streptorubin B, the main product being the syn isomer (41), which equilibrated over time to give the more stable anti configuration (40).…”
Section: Streptorubin B: a Recently Synthesized Antibiotic From Red Pmentioning
confidence: 99%
“…As a result, they turned to a comparison of the EI mass spectra. From this they found that synthetic butylcycloheptylprodigiosin (34a) and synthetic streptorubin B (34b) 34 showed characteristic differences in their EI mass spectra, with the data attributed to natural butylcycloheptylprodigiosin matching the mass spectrum of synthetic streptorubin B (34b) extremely well. On this basis, they concluded that butylcycloheptylprodigiosin (34a) was unlikely to represent a genuine natural product.…”
mentioning
confidence: 93%
“…5 This stereochemical assignment was confirmed by enantioselective total synthesis and X-ray crystallographic analysis. 6 Chiral high pressure liquid chromatography (HPLC) comparisons of 2 isolated from S. coelicolor with chemically synthesized (7′S)-, (7′R)-, and (7′RS)-streptorubin B showed that the natural material consists of the anti-(7′S), syn-(7′S), and anti-(7′R) isomers in an approximately 88:7:5 ratio. 5,6 The biosynthesis of undecylprodigiosin 1 and streptorubin B 2 in S. coelicolor has been extensively studied.…”
Section: ■ Introductionmentioning
confidence: 99%